Nagari Fund Management for Community Empowerment in Nagari IV Koto Hilie District of Batang Kapas Regency of Pesisir Selatan Province of West Sumatera - Agni Grandita Permatasari (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
This study sought to elaborate on the management of funds for the nagari communityempowerment program, the factors that influence it, as well as the efforts made by thenagari government. The method used in this research was descriptive qualitative andthe data collection method were through interviews, documentation, observation andtriangulation. Data were analyzed using data reduction techniques, as well as a datadisplay, SWOT analysis and Litmus Test. The results showed that the nomination ofempowerment programs were very minimal. Inhibiting factors included a lack ofoversight and advisory functions, the lack of skills/qualifications of nagari apparatus,lack of technological facilities, low community initiatives, as well as the low level ofpublic confidence on government. While the supporting factors, namely the largeamount of fund that recieved, efforts to increase the empowerment program in line withthe priority programs of the South Pesisir Regency, the documents that includeactivities RKPNagari empowerment, and the homogeneous structure of society bringhopes for improving empowerment program. Nagari government has made severalefforts, namely socialization, providing technological devices independently, theinitiative to make coordination with the regency government.